DETERMINASI SISTEM MERIT DAN GOOD GOVERNANCE TERHADAP KUALITAS KERJA - Diah Aryanti; Denok Kurniasih (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
The State Civil Apparatus (ASN) is a crucial part of the government. The implementation of the Merit System must be backed by excellent governance because it is one of the reform tools the government uses to achieve a high level of government performance. The purpose of this study is to investigate how the merit system and sound governance impact the caliber of output. The population of this study consisted of every PNS employed by the Banyumas district government. At 350 ASN, the sample is proportionally determined. Path analysis is a method used in data analysis. The findings indicated that the merit system and sound governance had an impact on the caliber of resources and personnel.